Pneumococcal conjugate vaccine in HIV-infected and HIV-exposed, uninfected children. (4th May 2017) - Jallow, Sabelle; Madhi, Shabir A.
ABSTRACT: Introduction : Incidence of invasive pneumococcal disease (IPD) among HIV-infected children is 20–40 fold greater compared to HIV-uninfected children, including among HIV-infected children on antiretroviral therapy (ART). Also, HIV-exposed, uninfected children have 2.7-fold greater risk of IPD compared to HIV-unexposed children. Areas covered : We reviewed studies identified on Pubmed database with the terms 'PCV' and 'HIV'; studies involving adults only were excluded. Expert commentary : While ART and pneumococcal conjugate vaccines (PCV) have reduced IPD morbidity and mortality in HIV-infected children, ART-naïve and immunosuppressed children have inferior immunogenicity to most PCV serotypes; highlighting the need for concomitant use of ART with PCV. Furthermore, studies to determine optimal PCV dosing schedules, timing and number of doses, are urgently required to ensure sustained vaccine efficacy in HIV-infected children.